* Measuring relief of dysphagia in patients with obstructing oesophageal malignancy; a pilot study using the EORTC OES-24 questionnaire in patients undergoing self-expanding metal stents (SEMS) insertion or chemotherapy. (13th March 2011) - Fisher, N; Corbett, C
Abstract : Introduction: There is no clear guidance on achieving relief of dysphagia for patients who have obstructing oesophageal malignancy. There are several approaches available, including endoscopic techniques, chemotherapy or radiotherapy. However there is limited comparative evidence for each technique. We have explored usage of the 20-item EORTC OES-24 questionnaire to help measure the effect of intervention on key symptoms in two patient groups treated with typical interventions. Methods: Patients with obstructing malignancy were selected prior to intervention with SEMS (Boston Oesophageal II stents) or chemotherapy (epirubicin, cisplatin and 5-fluorouracil). Chemotherapy was given as neo-adjuvant therapy prior to surgery or as first-line therapy in inoperable disease, while SEMS were used in patients with inoperable malignancy. Questionnaires were completed immediately prior to and 4 weeks after intervention was started. In this questionnaire, all scores range between 1 (for 'not at all') and 4 (for 'very much'). Results: 15 stent patients and 13 chemotherapy patients were recruited over a 12-month period. In the stent group, mean dysphagia scores for solids improved from 1.3 to 2.1 after treatment (p<0.01, Student t test). There were also significant improvements in other scores for enjoyment of food. There was no change in pain scores. However, the overall health anxiety score worsened from 2.8 to 3.5 (p<0.01). In the chemotherapy group, mean dysphagia scores improved from 2.4 to 3.1 after first chemotherapy (p<0.01) and there was an improvement in overall health score (3.5 to 2.9, p<0.01). Conclusion: For patients with obstructing oesophageal malignancy, this pilot study suggests an overall symptomatic benefit after SEMS, but with progressive anxiety, while patients undergoing neo-adjuvant therapy have an overall symptomatic benefit without anxiety. The EORTC OES-24 questionnaire may thus be a useful tool to measure benefit in patients undergoing new interventions for oesophageal malignancy.